SMARCA5 restricts chromatin accessibility to promote male meiosis and fertility in mammals - Shubhangini Kataruka; Aushaq B. Malla; Shannon R. Rainsford; Benjamin William Walters; Rachel A. Heuer; Kira L. Marshall; Bluma J. Lesch (Proceedings of the National Academy of Sciences, 2025)
Establishment of correct chromatin configuration in male meiosis is essential for sperm formation and male fertility. However, how chromatin remodeling contributes to meiotic progression in male germ cells is not well understood. Here, we find that the ISWI family ATP-dependent chromatin remodeling factor SMARCA5 (SNF2H) plays a critical role in regulating meiotic prophase progression during spermatogenesis in mice. Male mice with germ cell-specific depletion of SMARCA5 are infertile and unable to form sperm. Conditional knockout of Smarca5 results in meiotic progression failure, with abnormal spermatocytes appearing at the pachytene stage of meiosis I and subsequent accumulation of defects in chromosome synapsis, DNA repair, and transposon control, along with elevated rates of apoptosis. SMARCA5 interacts with known cofactors BAZ1A/ACF and BAZ2A/TIP5, as well as numerous DNA repair and recombination factors, in the testis. Single cell RNA sequencing confirmed failure to achieve a normal transcriptional state in premeiotic spermatogonia and during meiotic prophase, with reduced levels of meiotic gene transcripts and increasingly aberrant transcriptional states at later stages of spermatogenic development. Transcriptional misregulation in meiotic prophase was preceded by a widespread increase in chromatin accessibility in spermatogonia at promoters and repeat elements. Our findings suggest that SMARCA5 restricts chromatin accessibility in male germ cells to guide appropriate chromatin remodeling during meiotic recombination, contrasting with its role promoting chromatin accessibility during female meiosis.